2000
DOI: 10.1038/sj.bjp.0703713
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of JTV‐519, a novel cardioprotective drug, on potassium currents and experimental atrial fibrillation in guinea‐pig hearts

Abstract: We investigated the effects of JTV‐519 (4‐[3‐(4‐benzylpiperidin‐1‐yl)propionyl]‐7‐methoxy‐2,3,4,5‐tetrahydro‐1,4‐benzothiazepine monohydrochloride), a novel cardioprotective drug, on the repolarizing K+ currents in guinea‐pig atrial cells by use of patch‐clamp techniques. We also evaluated the effects of JTV‐519 on experimental atrial fibrillation (AF) in isolated guinea‐pig hearts. In atrial cells stimulated at 0.2 Hz, JTV‐519 in concentrations of 0.3 and 1 μM slightly prolonged the action potential duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…11 , 27 Other reports have shown that it can affect several sarcolemmal ion channels, e.g., L-type Ca 2+ channel. 25 , 28 , 29 In these studies, we found that JTV519(K201) had a potent effect on abnormal Ca 2+ release events in Purkinje cells. The drug reduced RMS F by 20% (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…11 , 27 Other reports have shown that it can affect several sarcolemmal ion channels, e.g., L-type Ca 2+ channel. 25 , 28 , 29 In these studies, we found that JTV519(K201) had a potent effect on abnormal Ca 2+ release events in Purkinje cells. The drug reduced RMS F by 20% (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…As shown in Table 1, K201 has been reported to have various actions at multiple sites in the cardiomyocyte, including non-specific multi-ion channel blocking effect (Kimura et al, 1999;Nakaya et al, 2000) and inhibition of SERCA (Loughrey et al, 2007). Most important is the finding that K201 stabilizes RyR2 and suppresses SR Ca 2+ leak by increasing the binding affinity for the FKBP12.6 to RyR2 (Wehrens et al, 2004).…”
Section: K201 (Or Jtv-519)mentioning
confidence: 94%
“…Inhibition of the muscarinic acetylcholine-receptor operated K current, delayed rectifier K + current, prolonged action potential duration (Nakaya et al, 2000) 1 and 3 M (2-3 min) …”
Section: Dantrolenementioning
confidence: 99%
“…Kiriyama et al demonstrated that JTV-519 inhibited the delayed rectifier K current in guinea-pig ventricular myocytes (24). Nakaya et al showed that JTV-519 exerted antiarrhythmic effects against atrial fibrillation by inhibiting repolarizing K currents in isolated guinea-pig hearts (25).…”
Section: Discussionmentioning
confidence: 99%